An efficient iron-catalyzed S-arylation of aryl and alkylthiols with aryl halides in the presence of water under aerobic conditions. Issue 34 (19th August 2015) - Sindhu, K.S.; Thankachan, Amrutha P.; Thomas, Anns Maria; Anilkumar, Gopinathan
Graphical abstract: Abstract: In this study, an environmentally benign FeCl3 ·6H2 O/l -proline catalytic system in the presence of TBAB was employed as a catalyst for the coupling reactions of aryl halides with aryl and alkyl thiols in water under aerobic conditions. The versatility, low cost, and environmental friendliness, in combination with high yields, makes the procedure noteworthy. This protocol offers a simple and efficient thioetherification method for aryl halides.